Halal Tourism and Its Misconceptions: Revisiting The Rejection of Non-Muslim Tourism Destinations - Rakhman Priyatmoko; Addin Maulana (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2022)
The term "halal tourism" is indeed recognized in Indonesia, nonetheless, its pros and cons are happening. Unlike any other non-Muslim countries such as Japan, South Korea, New Zealand, Taiwan, and Thailand, which tend to have less conflict between tourism stakeholders regarding the development of halal tourism, the rejection occurs in Indonesia as a country with a Muslim majority population. The rejection culminated in 2019 as a political year along with the presidential elections. The rejection of halal tourism occurs in tourism destinations such as Bali, Labuan Bajo, Toba, and Toraja known as the Muslim minority population area. Based on those issues, this study uses a qualitative approach to investigate the rejection reasons from the tourism stakeholders, to provide theoretical clarification on the stigma against halal tourism, and to analyze how halal tourism branding policy in tourism destinations. The result shows that the rejection of halal tourism by the tourism stakeholders was due to concerns that there would be a change in the destination’s image. To prevent prolonged debate and possible social conflict, the Indonesian government can use another term that sounds more moderate and acceptable for tourism stakeholders in non-Muslim destinations. Moreover, tourism stakeholders in each destination should take over the use of halal branding, so that the tourism policies adopted are regional initiatives (bottom-up policies).